2020
DOI: 10.1002/cncr.33239
|View full text |Cite
|
Sign up to set email alerts
|

Impact of health literacy on shared decision making for prostate‐specific antigen screening in the United States

Abstract: BackgroundCurrent guidelines endorse shared decision making (SDM) for prostate‐specific antigen (PSA) screening. The relationship between a patient's health literacy (HL) and SDM remains unclear. In the current study, the authors sought to identify the impact of HL on the rates of PSA screening and on the relationship between HL and SDM following the 2012 US Preventive Services Task Force recommendations against PSA screening.MethodsUsing data from the 2016 Behavioral Risk Factor Surveillance System, the autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
(35 reference statements)
2
19
0
Order By: Relevance
“…Men in the highest health literacy group reported the highest rates of PSA screening (42.2%; 95% confidence interval [95% CI], 40.5%‐43.9%). Screening rates among men reporting a discussion of the advantages with or without a discussion of the disadvantages of screening reported similarly high rates of PSA screening (48.4%‐49.4%), whereas those reporting no discussion had the lowest rates of PSA screening (8.2%) 4 . In regression analyses adjusted for available demographic and socioeconomic factors, those men with the highest health literacy reported the greatest odds of undergoing PSA screening (odds ratio [OR], 1.214; 95% CI, 1.051‐1.403), with higher educational level (OR, 1.444; 95% CI, 1.144‐1.822), higher income (OR, 1.463; 95% CI, 1.085‐1.972), and health care provider recommendation for screening (OR, 6.128; 95% CI, 5.272‐7.124) found to be associated with greater odds of undergoing PSA screening 4 .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Men in the highest health literacy group reported the highest rates of PSA screening (42.2%; 95% confidence interval [95% CI], 40.5%‐43.9%). Screening rates among men reporting a discussion of the advantages with or without a discussion of the disadvantages of screening reported similarly high rates of PSA screening (48.4%‐49.4%), whereas those reporting no discussion had the lowest rates of PSA screening (8.2%) 4 . In regression analyses adjusted for available demographic and socioeconomic factors, those men with the highest health literacy reported the greatest odds of undergoing PSA screening (odds ratio [OR], 1.214; 95% CI, 1.051‐1.403), with higher educational level (OR, 1.444; 95% CI, 1.144‐1.822), higher income (OR, 1.463; 95% CI, 1.085‐1.972), and health care provider recommendation for screening (OR, 6.128; 95% CI, 5.272‐7.124) found to be associated with greater odds of undergoing PSA screening 4 .…”
mentioning
confidence: 99%
“…Screening rates among men reporting a discussion of the advantages with or without a discussion of the disadvantages of screening reported similarly high rates of PSA screening (48.4%‐49.4%), whereas those reporting no discussion had the lowest rates of PSA screening (8.2%) 4 . In regression analyses adjusted for available demographic and socioeconomic factors, those men with the highest health literacy reported the greatest odds of undergoing PSA screening (odds ratio [OR], 1.214; 95% CI, 1.051‐1.403), with higher educational level (OR, 1.444; 95% CI, 1.144‐1.822), higher income (OR, 1.463; 95% CI, 1.085‐1.972), and health care provider recommendation for screening (OR, 6.128; 95% CI, 5.272‐7.124) found to be associated with greater odds of undergoing PSA screening 4 . Upon further interaction testing between health literacy and SDM, Nguyen et al found that higher health literacy was associated with a lower likelihood of undergoing PSA screening when SDM was present, although maximal SDM remained significantly associated with a greater likelihood of PSA screening across all health literacy levels 4 .…”
mentioning
confidence: 99%
See 3 more Smart Citations